Pengaruh Profitabilitas, Keputusan Investasi, Keputusan Pendanaan, Dan Keputusan Dividen Terhadap Economic Value Added (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2015-2017). - Fitria Putri Susanti; Jeni Susyanti; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
AbstractThis research was conducted to analyze the effect of profitability, investment decisions, funding decisions, and dividend decisions on economic value added. The sample in this study is a manufacturing company that is listed on the BEI in 2015-2017. The analytical method used is multiple linear regression with SPSS 14.0 for Windows software. The results of sampling using the purposive sampling method and those that meet the sample criteria are as many as 20 companies.Based on the results of hypothesis testing that has been done, it is concluded that simultaneous profitability, investment decisions, funding decisions, and dividend decisions affect the economic value added. Partially, profitability variables and dividend decision variables affect the economic value added. While investment decision variables and funding decision variables do not affect the economic value added.Keywords: Profitability (ROA), Investment Decisions (PER), Funding Decisions (DER), Dividend Decisions (DPR), and Economic Value Added (EVA).